EFFECT OF MEDICAL WASTE MANAGEMENT TRAININGS ON BEHAVIOR CHANGE AMONG DOCTORS VERSUS NURSES AND PARAMEDICAL STAFF IN PAKISTAN - Kumar, Ramesh; Somrongthong, Ratana; Ahmed, Jamil (Journal of Ayub Medical College Abbottabad, 2016)
Background: Healthcare waste management is a neglected issue in hospitals of developing countries due to poor practices among health staff. This study was aimed to determine the differences in knowledge, attitude and practices of physicians versus nursing and paramedical staff about standard health care waste management (HCWM). Method: This quasi-experimental study was conducted among healthcare workers of the two tertiary care hospitals in Rawalpindi. A total of 138 hospital workers in intervention and 137 in control hospital were given training on HCWM. Subjects were followed up at one year and after 18 months of the intervention. Results: We found that nursing and paramedical staff was more knowledgeable and compliant with the HCWM standards, knowledge and practices as compared to physicians. A higher proportion of nursing and paramedical staff was able to retain more of high level of knowledge but more of the doctors had achieved and retained positive attitudes towards HCWM standards after the training. More of nursing and paramedical staff also had good HCWM practices; both at first as well as second follow up. Conclusion: As nursing and paramedical staff was more knowledgeable and practiced optimum standards they needed to be rewarded adequately and given further regular trainings to help them maintain their knowledge and best practices about HCWM. As HCWM and patient safety standards keep on changing regularly, the hospital workers especially doctors need to be focused to comply with the standard practices in hospitals. Keywords: Hospital workers; Waste management; Knowledge attitude and practice; Intervention; Training